Mechanisms underlying effects of kiwifruit on intestinal function shown by MRI in healthy volunteers. Issue 6 (31st January 2019) - Wilkinson‐Smith, Victoria; Dellschaft, Neele; Ansell, Juliet; Hoad, Caroline; Marciani, Luca; Gowland, Penny; Spiller, Robin
Summary: Background: Chronic constipation affects approximately 17% of the population worldwide and remains an important unmet need since patients are often dissatisfied with treatment. Kiwifruit may offer an alternative to traditional laxatives and have been shown to increase stool volume, frequency and improve consistency. Aims: Using non‐invasive MRI techniques, we assessed the effect of ingestion of kiwifruit on fluid distribution in the intestines and bowel function. Methods: Two period crossover trial of kiwifruit vs control in healthy adults. Intervention: two kiwifruits twice daily vs isocaloric control (maltodextrin) twice daily, consumed for a total of 3 days. Subjects underwent MRI scanning fasted and at hourly intervals for 7 hours on the third day. Primary outcome: T1 relaxation time of ascending colon (T1AC) using MRI. Secondary outcomes: Small bowel water content (SBWC), colonic volume, gut transit time, T1 of descending colon, stool frequency and form. Results: Fourteen volunteers completed the study. T1AC was higher after kiwifruit ingestion (P = 0.029) during the second half of the day (when meal residue would be expected to reach the AC, AUC T1 T240‐420 minutes; mean (SD) 137 (39) s*minute with kiwifruit versus 108 (40) s*minute with control. SBWC (P < 0.001), colon volumes (P = 0.004), as well as stool frequency (1.46 ± 0.66 with kiwifruit vs 1.14 ± 0.46 stools per day with control; P = 0.034) and stool form score (Bristol Stool Chart score 4.1 (0.9) with kiwifruit versus 3.4 (0.7) with control; P = 0.011) were markedly increased in participants consuming kiwifruit compared to control. Conclusion: Consumption of kiwifruit in healthy volunteers increases water retention in the small bowel and ascending colon and increases total colonic volume. The data may explain the observed increase in stool frequency and looser stool consistencies, suggesting that kiwifruit could be used as a dietary alternative to laxatives in mild constipation.